Gut fungal community composition analysis of myostatin mutant cattle prepared by CRISPR/Cas9 - Gao, Li; Wang, Song; Yang, Miaomiao; Wang, Lili; Li, Zhen; Yang, Lei; Li, Guangpeng; Wen, Tong (Frontiers in Veterinary Science, 2023)
Myostatin (MSTN) regulates muscle development and body metabolism through a variety of pathways, and is a core target gene for gene editing in livestock. Gut fungi constitute a small part of the gut microbiome and are important to host health and metabolism. The influence of MSTN mutations on bovine gut fungi remains unknown. In this study, ITS high-throughput sequencing was conducted to explore the composition of gut fungi in MSTN mutant (MT) and wild-type (WT) cattle; 5861 operational taxonomic units (OTUs) were detected and classified into 16 phyla and 802 genera. The results of alpha diversity indicated that no notable divergence existed between WT and MT cattle; however, significant differences existed in the composition of the fungal communities. Eight phyla and 18 genera were detected. According to the prediction of fungal function, saprotroph fungi were significantly more abundant in the MT group. Correlation analysis between gut fungal and bacterial communities revealed that MSTN mutations directly changed the gut fungal composition, and at the same time influenced some fungi and bacteria by indirectly regulating the interaction between microorganisms, which further affected host metabolism. This study analyzed the role of MSTN mutation in regulating the host metabolism of intestinal fungi and provided a theoretical basis for the relationship between MSTN and gut fungi.